Knowledge and attitude of patients with diabetes mellitus in Primary Health Care - Suelen Cordeiro Assunção; Alisson Pereira Fonseca; Marise Fagundes Silveira; Antônio Prates Caldeira; Lucinéia de Pinho (Universidade Federal do Rio de Janeiro, 2017)
Abstract Objective: To evaluate the knowledge and attitude of patients with diabetes mellitus in Primary Health Care and associated factors. Methods: Cross-sectional, quantitative and analytical study with 353 patients with type 2 diabetes mellitus in Family Health Strategy units. The Knowledge and Psychological Attitudes Questionnaires were used for data collection, as well as a script with sociodemographic, economic and clinical data. Results: The majority of the population was female (73.1%), aged more than 50 years (81.5%), diagnosed for more than five years (54.9%) and with a per capita income of up to half a minimum wage (59.3%). The scores of knowledge and attitude were low. Age (p = 0.001) and level of education (p = 0.002) were variables associated with knowledge about diabetes mellitus. Conclusion: Users had a low level of knowledge about diabetes, indicating an unsatisfactory result in self-care and mainly a negative attitude towards coping with this disease.